The Business Cycle as a Moderator of Financing for Financing Risk of Islamic Commercial Banks in Indonesia - Much Maftuhul Fahmi; Nanik Wahyuni; Yuniarti Hidayah Suroso Putra (Universitas Airlangga, 2023)
ABSTRACT Islamic banking is undoubtedly faced with several potential financing risks, with the three largest financing contracts (Mudharaba, Musharaka, and Murabaha) that reduce the financial performance of Islamic banks. The potential risk is strengthened if the stability of national economic growth is contracted. Therefore, this research aims to investigate the impact of Mudharaba, Musharaka, and Murabaha financing on Financing Risk moderated by the business cycle and the relationship between Financing Risk and the Financial Performance of Islamic Commercial Banks. The sample of this study was 12 Islamic Commercial Banks in Indonesia during the period 2017-2021. The Data were then analyzed using the technique of Moderated Regression Analysis (MRA). Researchers found that Musharaka financing has a significant positive effect on Financing Risk, Mudharaba and Murabaha Financing has an insignificant effect on Financing Risk, and Financing Risk has a significant negative effect on Financial Performance. The Business Cycle does not moderate the Financing of Mudharaba, Musharakah, and Murabaha on Financing Risk. The results can encourage the Islamic Commercial Bank to evaluate the distribution strategy of Musharaka financing, optimize the distribution of Mudharaba and Murabaha financing, and prepare financing strategies that do not depend on macroeconomic conditions. Keywords: Financing Risk, Financing, Business Cycle, Financial Performance. ABSTRAK Perbankan syariah dengan tiga akad pembiayaan terbesar (Mudharaba, Musharaka, dan Murabaha) dihadapkan pada sejumlah potensi risiko pembiayaan yang menurunkan kinerja keuangan Bank Syariah. Potensi risiko tersebut menguat jika stabilitas pertumbuhan ekonomi nasional juga terganggu atau mengalami kontraksi. Oleh karena itu, penelitian ini hendak mengkaji pengaruh Pembiayaan Mudharaba, Musharaka, dan Murabaha terhadap Risiko Pembayaran dengan dimoderasi oleh Siklus Bisnis, dan sekaligus menguji hubungan antara Risiko Pembayaran dan Kinerja Keuangan Bank Syariah. Sampel penelitian ini adalah 12 Islamic Commercial Bank di Indonesia selama periode 2017-2021. Data tersebut kemudian dianalisis dengan menggunakan teknik Moderated Regression Analysis (MRA). Peneliti menemukan bahwa Pembiayaan Musharaka berpengaruh positif signifikan terhadap Risiko Pembiayaan, Pembiayaan Mudharaba dan Murabaha tidak berpengaruh signifikan terhadap Risiko Pembiayaan, dan Risiko Pembiayaan berpengaruh negatif signifikan terhadap Kinerja Keuangan. Adapun Siklus Bisnis tidak dapat memoderasi Pembiayaan Mudharaba, Musharaka, dan Murabaha terhadap Risiko Pembiayaan. Hasil penelitian ini dapat menjadi evaluasi bagi Islamic Commercial Bank agar dapat mengevaluasi strategi penyaluran pembiayaan Musharaka, mengoptimalkan penyaluran pembiayaan Mudharaba dan Murabaha, dan mempersiapkan strategi pembiayaan yang tidak bergantung pada kondisi makro ekonomi. Kata Kunci: Risiko Pembiayaan, Pembiayaan, Siklus Bisnis, Kinerja Keuangan. REFERENCES Abdillah, W., & Hartono, J. (2015). Partial least square (PLS) alternatif structural equation modelling (SEM) dalam penelitian bisnis. CV. Andi Offset. Abdul-rahman, A., & Nor, S. M. (2016). Challenges of profit-and-loss sharing financing in Malaysian Islamic banking. Malaysian Journal of Society and Space 12, 2(2), 39–46. Adzimatinur, F., & Manalu, V. G. (2020). The impact of mudharabah and musharakah based financing to credit risk. 1st Annual Conference of Ihtifaz: Islamic Economics, Finance, and Banking, 127–134. Aiyubbi, D. E., Widarjono, A., & Amir, N. (2022). The impact of sectoral financing diversification on non-performing financing of Islamic rural banks. Jurnal Ekonomi Syariah Teori Dan Terapan, 9(2), 140–155. https://doi.org/https://doi.org/10.20473/vol9iss20222pp140-155 Al-Harbi, A. (2020). Banks' profitability in an Islamized financial system: Comparative study between Iran and Sudan. International Journal of Islamic Banking and Finance Research, 4(1), 8–14. https://doi.org/10.46281/ijibfr.v4i1.498 Alarussi, A. S., & Alhaderi, S. M. (2018). Factors affecting profitability in Malaysia. Journal of Economic Studies, 45(3), 442–458. https://doi.org/10.1108/JES-05-2017-0124 Alper, D., & Anber, A. (2011). Bank specific and macroeconomics determinant of commercial banks profitability empirical evidence from Turkey. Business and Economics Research Journal, 2, 138–152. Anik, A., & Prastiwi, I. E. (2019). Macro economic challenges and third party funds of Islamic commercial banks in Indonesia. Shirkah: Journal of Economics and Business, 3(1), 127-151. https://doi.org/10.22515/shirkah.v3i1.208 Arikunto. (2006). Metode penelitian: Prosedur penelitian suatu pendekatan praktek. PT. Rineka Cipta. Azizah, S. N., & Mukaromah, S. (2020). The Effect of murabaha financing, profit sharing financing, intellectual capital, and non performing financing (NPF) on financial performance. Jurnal Reviu Akuntansi Dan Keuangan, 10(1), 150–160. https://doi.org/10.22219/jrak.v10i1.11323 Belkhaoui, S., Alsagr, N., & van Hemmen, S. F. (2020). Financing modes, risk, efficiency and profitability in Islamic banks: Modeling for the GCC countries. Cogent Economics and Finance, 8(1), 1-25. https://doi.org/10.1080/23322039.2020.1750258 Ben Bouheni, F., Obeid, H., & Margarint, E. (2022). Nonperforming loan of European Islamic banks over the economic cycle. Annals of Operations Research, 313(2). https://doi.org/10.1007/s10479-021-04038-8 Bodie, Z., Kane, A., & Marcus, A. J. (2014). Investments. Mc Graw Hill Education. Booth, J. R., Officer, D. T., & Henderson, G. V. (1985). Commercial bank stocks, interest rates, and systematic risk. Journal of Economics and Business, 37(4), 303–310. https://doi.org/10.1016/0148-6195(85)90024-4 BPS. (2021). [Seri 2010] Laju Pertumbuhan PDB Seri 2010, 2010(September), 1–10. https://www.bps.go.id/indikator/indikator/view_data/0000/data/104/sdgs_17/1 Danlami, M. R., Abduh, M., & Abdul Razak, L. (2022). CAMELS, risk-sharing financing, institutional quality and stability of Islamic banks: evidence from 6 OIC countries. Journal of Islamic Accounting and Business Research, 13(8), 1155–1175. https://doi.org/10.1108/JIABR-08-2021-0227 Enqvist, J., Graham, M., & Nikkinen, J. (2014). The impact of working capital management on firm profitability in different business cycles: Evidence from Finland. Research in International Business and Finance, 32, 36–49. https://doi.org/10.1016/j.ribaf.2014.03.005 Fianto, B. A., Gan, C., & Hu, B. (2019). Financing from Islamic microfinance institutions: evidence from Indonesia. Agricultural Finance Review, 79(5), 633–645. https://doi.org/10.1108/AFR-10-2018-0091 Financial Service Authority. (2021). Snapshot perbankan syariah September 2021. In Financial Service Authority. Financial Service Authority. (2022). Sharia Banking Statistic. Hasanah, R., & Septiarini, D. F. (2020). The effect of CAR, ROA, BI 7-day rate, and inflation on non-performing home financing in sharia general banks for the 2016-2018 period. Jurnal Ekonomi Syariah Teori Dan Terapan, 7(4), 774–794. https://doi.org/https://doi.org/10.20473/vol7iss20204pp774-794 Hosen, M. N., & Muhari, S. (2019). Non-performing financing of Islamic rural bank industry in Indonesia. Banks and Bank Systems, 14(1), 20–28. https://doi.org/10.21511/bbs.14(1).2019.03 Ijaiya, M., Jimoh, A. T., Attah, J. A., Nafiu, A. I., Polytechnic, F., & State, K. (2021). Murabaha-related credit risk and financial performance of Islamic banks in Africa. International Journal of Islamic Banking and Finance Research, 5(1), 60–69. https://doi.org/10.46281/ijibfr.v5i1.1279 Lisa, O., Dahlan, A., & Gustopo, A. A. (2022). Non-performing financing as a medium of sharia cooperative performance in East Java non-performing financing sebagai pemediasi kinerja koperasi syariah di Jawa Timur. Jurnal Ekonomi Syariah Teori Dan Terapan, 9(6), 863–873. https://doi.org/10.20473/vol9iss20226pp863-873 McQueen, G., & Roley, V. V. (1993). Stock prices news and business conditions. The Review of Financial Studies, 6(3), 683–707. Mutamimah, M., & Saputri, P. L. (2022). Corporate governance and financing risk in Islamic banks in Indonesia. Journal of Islamic Accounting and Business Research, Vol. ahead-of-print No. ahead-of-print. https://doi.org/10.1108/JIABR-09-2021-0268 Nosheen, & Rashid, A. (2019). Business orientation, efficiency, and credit quality across business cycle: Islamic versus conventional banking. Are there any lessons for Europe and Baltic States? Baltic Journal of Economics, 19(1), 105–135. https://doi.org/10.1080/1406099X.2018.1560947 Ogunleye, R. W. (2001). Sensitivity of bank stock return to market and interest rate risks. NDIC Quarterly, 11(1), 57–77. Omer Mustafa, O. A. (2020). Why do Islamic banks concentrating finance in murabaha mode? performance and risk analysis (Sudan: 1997-2018). International Business Research, 13(7), 208-223. https://doi.org/10.5539/ibr.v13n7p208 Pham, H. S. T., & Nguyen, D. T. (2020). The effects of corporate governance mechanisms on the financial leverage–profitability relation: Evidence from Vietnam. Management Research Review, 43(4), 387–409. https://doi.org/10.1108/MRR-03-2019-0136 Priyadi, U., Utami, K. D. S., Muhammad, R., & Nugraheni, P. (2021). Determinants of credit risk of Indonesian SharÄ«Ê¿ah rural banks. ISRA International Journal of Islamic Finance, 13(3), 284–301. https://doi.org/10.1108/IJIF-09-2019-0134 Purba, N. S., & Darmawan, A. (2018). Pengaruh pertumbuhan produk domestik bruto dan inflasi terhadap non performing finance bank syariah. Jurnal Administrasi Bisnis (JAB), 61(2), 172. Rahardja, P., & Manurung, M. (2005). Teori ekonomi makro. Fakultas Ekonomi Universitas Indonesia. Rahmah, A. Z., & Armina, S. H. (2020). Macro and micro determinants of the non-performing finance: The case of Indonesian Islamic bank. Jurnal Ekonomi & Keuangan Islam, 6(1), 34–41. https://doi.org/10.20885/jeki.vol6.iss1.art4 Ringle, C. M., Wende, S., & Becker, J.-M. (2015). SmartPLS 3. In Boenningstedt: SmartPLS GmbH. Retrieved from http://www.smartpls.com. Rizvi, S. A. R., Narayan, P. K., Sakti, A., & Syarifuddin, F. (2020). Role of Islamic banks in Indonesian banking industry: An empirical exploration. Pacific Basin Finance Journal, 62(October 2018), 101117. https://doi.org/10.1016/j.pacfin.2019.02.002 Sabrina, S., & Majid, M. S. A. (2020). The reluctance phenomenon of Islamic banks to offer profit-loss sharing financing. JEJAK: Journal of Economics and Policy, 13(2), 242–264. https://doi.org/10.15294/jejak.v13i2.23891 Sahyouni, A., & Wang, M. (2019). Liquidity creation and bank performance: Evidence from MENA. ISRA International Journal of Islamic Finance, 11(1), 27–45. https://doi.org/10.1108/IJIF-01-2018-0009 Sandika, M. T. (2013). Hubungan faktor-faktor ekonomi makro terhadap profitabilitas PT Bank Central Asia tbk periode Juli 2005 – Mei 2011. Semnas Fekon: Optimisme Ekonomi Indonesia 2013, Antara Peluang dan Tantangan. Schoon, N. (2016). Modern Islamic banking: Products and processes in practice. John Wiley & Sons Ltd. Setiawan, U. N. A., & Indriani, A. (2016). Pengaruh dana pihak ketiga (DPK), capital adequacy ratio (CAR), dan non performing financing (NPF) terhadap profitabilitas bank syariah dengan pembiayaan sebagai variabel intervening. Jurnal Riset Akuntansi & Keuangan, 5(3), 1535–1540. Sugiyono. (2014). Metode penelitian pendekatan kuantitatif, kualitatif, dan R&D. Alfabeta. Supriani, I., & Sudarsono, H. (2018). Analisis pengaruh variabel mikro dan makro terhadap NPF perbankan syariah di Indonesia. Equilibrium: Jurnal Ekonomi Syariah, 6(1), 1-18. https://doi.org/10.21043/equilibrium.v6i1.3040 Sutrisno, S., & Widarjono, A. (2022). Is profit – loss-sharing financing matter for Islamic bank's. 10(207), 1–12. https://doi.org/10.3390/risks10110207 Suzuki, Y., Uddin, S. M. S., & Islam, A. K. M. R. (2020). Incentives for conventional banks for the conversion into Islamic banks: evidence from Bangladesh. Journal of Islamic Accounting and Business Research, 11(2), 273–287. https://doi.org/10.1108/JIABR-03-2017-0031 Tran, S. H., & Nguyen, L. T. (2020). Financial development, business cycle and bank risk in Southeast Asian countries. Journal of Asian Finance, Economics and Business, 7(3), 127–135. https://doi.org/10.13106/jafeb.2020.vol7.no3.127 Umami, D. R., & Rani, L. N. (2021). Factors affecting non-performing financing of sharia rural banks for 2015-2019 period. Jurnal Ekonomi Syariah Teori Dan Terapan, 8(4), 483–495. https://doi.org/https://doi.org/10.20473/vol8iss20214pp483-495 Warninda, T. D., Ekaputra, I. A., & Rokhim, R. (2019). Do mudarabah and musharakah financing impact Islamic bank credit risk differently? Research in International Business and Finance, 49(September 2017), 166–175. https://doi.org/10.1016/j.ribaf.2019.03.002 Widarjono, A., Anto, M. B. H., & Fakhrunnas, F. (2020). Financing risk in Indonesian Islamic rural banks: Do financing products matter? Journal of Asian Finance, Economics and Business, 7(9), 305–314. https://doi.org/10.13106/JAFEB.2020.VOL7.NO9.305 Yahya, D. R. (2019). Pengaruh pengelolaan modal kerja terhadap profitabilitas dan likuiditas dengan siklus bisnis sebagai variabel moderasi. Media Mahardhika, 17(3), 400–413. https://doi.org/https://doi.org/10.29062/mahardika.v17i3.96 Zannati, R., & Hendryadi. (2019). Determinan non performing financing perbankan syariah: Perspektif makro ekonomi. SERAMBI: Jurnal Ekonomi Manajemen Dan Bisnis Islam, 1(3), 91–100. https://doi.org/https://doi.org/10.36407/serambi.v1i3.126